Analisis Sistem Dan Kompleksitas Pelayanan Rumah Sakit - Tarisa Rahmawati; Alda Ramadhika (STIE Amkop Makassar, 2024)
A hospital is a health facility that provides health services evenly by prioritizing disease healing and health recovery that is carried out harmoniously and integrated. The method used in this study is literature review, and involves a number of activities involving library data collection on improving the quality management of health services in hospitals. The results and discussion in this study are health services are efforts made alone or together in an organization to maintain and improve health, prevent and treat diseases and restore health aimed at individuals, groups and communities. Health services in hospitals have a high level of complexity (capital-intensive, labor-intensive and technology-intensive) which is indispensable in improving public health status. Currently, quality health services are a basic need that everyone needs. Good quality health care can cause satisfaction in every patient. In an effort to maintain the quality of health services in hospitals, the nursing profession plays an important role and as the main key in hospital services.